Digital Word of Mouth and Consumer Decisions in Islamic Banking: Unpacking the Mediating Role of Trust - Dedi Supiyadi; Ratih Hurriyati; Puspo Dewi Dirgantari; Nugraha Nugraha; Chuanchen BI (Sinergi International Journal of Management and Business, 2026)
This study examines how electronic word-of-mouth (e-WOM) influences consumer purchase intention in Indonesia’s Islamic banking sector, with trust positioned as a central mediating mechanism. Using survey data from 177 users of Islamic digital banking services and Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings reveal that while e-WOM significantly enhances consumer trust, it does not exert a direct effect on purchase intention. Instead, trust fully mediates the e-WOM–purchase intention relationship, indicating that digital social information becomes behaviorally relevant only after it is internalized as institutional and Sharia-based trust. This study offers a clear theoretical contribution by integrating the Information Adoption Model (IAM) and the Theory of Planned Behavior (TPB) within the context of Islamic banking, demonstrating that information credibility alone is insufficient to drive intention without trust-based evaluation. Empirically, the Indonesian context is particularly salient given the persistent gap between the country’s large Muslim population and the relatively low market share of Islamic banking, highlighting trust as a critical psychological barrier. The findings extend digital marketing and Islamic finance literature by clarifying the conditional pathway through which e-WOM influences intention in high-risk, value-based financial services. Managerially, the results emphasize the importance of credible, transparent, and value-aligned digital communication strategies to cultivate trust.